Capacity Building at the Kurdistan Region Statistics Office Through Data Collection - Shmuel Abramzon, Nicholas Burger, Bonnie Ghosh-Dastidar, Peter Glick, Krishna B. Kumar, Francisco Perez-Arce, Alexan (RAND Corporation, 2014)
Comprehensive and reliable statistics on a region make it possible to identify pressing needs, track progress, plan future development, and create successful policies. The Kurdistan Region of Iraq (KRI) lacks the statistics it needs to improve infrastructure, encourage development, attract investment, and sustain economic growth. In a previous study, we assessed existing institutional arrangements for collecting and sharing data within the Kurdistan Regional Government (KRG); assessed the data and information infrastructure available in the KRI; identified KRG policy priorities to ensure that collected data are relevant to policymaking; identified data items that need to be collected for each priority area; and recommended data collection methods, institutional arrangements, and a roadmap for implementing recommendations, including steps needed to build human-resource capacity within the KRG and the Kurdistan Regional Statistics Organization (KRSO).1 The KRG-funded follow-up study documented here aimed to provide assistance in implementing the recommendations made during the course of the efforts just described. The overarching goal of this study was to assist the KRI’s central statistical organization—the KRSO—and the KRG in building the capacity to undertake the recommended data collection. We worked closely with the KRSO and in consultation with relevant ministries to prepare, conduct, and analyze from start to finish a survey critical to KRG policymaking, the Kurdistan Region Labor Force Survey. This survey will make possible ongoing monitoring of trends in labor force participation, unemployment, and other indicators for the region. The RAND Corporation provided the KRSO with overall guidance and analytical and hands-on training. Further, by being involved in the complete life cycle of the survey, from conception through data collection to policy analysis, and by being responsible for the final execution and analysis of the surveys, KRSO staff benefited from learning by doing. The primary intended audience for this report is KRG policymakers and KRSO staff. The report is intended to serve this audience as (1) a summary of our activities for this project, (2) a presentation of key results from the labor force survey, and (3) a reference guide. By relegating most of the technical details to appendixes, we also aim to make this report accessible to general readers who may be interested in the KRI economy; how capacity building for central statistical organizations can be carried out; and in the design, implementation, and analysis of labor force surveys, especially in the context of emerging economies.